2000
DOI: 10.1177/019262330002800320
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Use of Transgenic Animals for Carcinogenicity Testing: Considerations and Implications for Risk Assessment

Abstract: Advances in genetic engineering have created opportunities for improved understanding of the molecular basis of carcinogenesis. Through selective introduction, activation, and inactivation of specific genes, investigators can produce mice of unique genotypes and phenotypes that afford insights into the events and mechanisms responsible for tumor formation. It has been suggested that such animals might be used for routine testing of chemicals to determine their carcinogenic potential because the animals may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 105 publications
(187 reference statements)
0
57
0
Order By: Relevance
“…Transgenic and null mutant ('knockout') animal models also offer an important opportunity to identify and study both carcinogens and chemopreventive agents [196,197]. The analysis of the available data on transgenic and mutant mice has shown that only few models represent examples of life span extension [195].…”
Section: Effect Of Genetic Modifications Of Aging On Carcinogenesismentioning
confidence: 99%
“…Transgenic and null mutant ('knockout') animal models also offer an important opportunity to identify and study both carcinogens and chemopreventive agents [196,197]. The analysis of the available data on transgenic and mutant mice has shown that only few models represent examples of life span extension [195].…”
Section: Effect Of Genetic Modifications Of Aging On Carcinogenesismentioning
confidence: 99%
“…The lines proposed bear altered forms of genes that are known to be mutated in certain human cancers. The Tg.AC line carries an activated form of the v-Ha-ras oncogene, the p53 heterozygote KO possesses an inactivated copy of the p53 tumor suppressor gene, the rasH2 transgenic mouse bears the human c-Ha-ras gene, and the XPA heterozygote KO mouse is deficient in nucleotide excision repair (69). The ras family of oncogenes is activated by point mutations, and such activation has been implicated in various human and animal cancers (70).…”
Section: Application Of Gem For Drug Development and Safety Testmentioning
confidence: 99%
“…The p53 +/7 mice have a low incidence of spontaneous tumours up to 9 months but rates increased substantially thereafter. Thus, the p53 +/7 knockout mouse offers a phenotypically stable carcinogenicity model, developing tumours during the 6-month study period only in response to genotoxic agents (10). Although more sensitive and showing a shorter latent period for tumours, the single functional gene in the p53 +/7 mouse model allows some nucleotide excision repair of DNA damage relative to homozygous p53 7/7 knockout mice, but the reduced ability of p53 +/7 mice to repair DNA damage is an additional possible origin for the earlier and more frequent appearance of tumours in these mice, compared to wild-type mice (11).…”
Section: Introductionmentioning
confidence: 99%